Advancing Gender-Inclusive Climate Change Adaptation: Overcoming Inequality through Sustainable Pathways - Begum, Tarana (The Jahangirnagar Review, 2024)
This study investigates how rural women in flood-prone areas are involved in adaptation actions. The study focuses on gender inequalities in climate-resilient adaptation and sustainable development pathways. The research evaluates the attainability of reducing gender inequality through a sustainable adaptation process. 53 women from Sirajganj Sadar Upazila who were involved in government or non-government adaptation and community awareness programmes were interviewed. Addressing the gender inequality within the climate change policy is deemed critical in the context of Bangladesh and around the globe. This study shows that if gender discrepancies persist, women will face more setbacks as the effects of climate change. To overcome this, plans must prioritise disadvantaged women's inclusion in adaptation programmes and secure their access to resources. Government and non-governmental efforts should provide inclusive support to encourage women's active participation.